Технологія безкранового монтажу покрівель із легких металевих конструкцій - Попов, Д. С.; Чебанов, Т. Л. (Ways to Improve Construction Efficiency, 2014)
Article deals with the installation of roofs made of lightweight metal. From finding the rational design and technological solutions assembling the authors performed a patent search . The existing links to local inventors , inventors’ certificates , literature review , structured findings do allow classification of implementing these techniques in practice.